2017
DOI: 10.1021/acsaem.7b00086
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Upgrading by Transition Metal Carbides

Abstract: The separation of carbon dioxide (CO2) from methane (CH4) is critical in biogas upgrading, requiring materials with high selectivity towards one of the two gas components. Hereby we ASSOCIATED CONTENTThe Supporting Information is available free of charge on the ACS Publications website. Additional computational details, list of adsorption energies and contributions, and geometric descriptors, top views of ad-sorbate structures, brief explanation of the used rate model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Energies for each minimum and transition state are shown in Table 1. Recently, Illas et al, 21 studied chemically adsorbed CO 2 on the {001} surface of the same series of TMCs and, whilst no other surfaces or states were considered, the available results are in excellent agreement with ours (see 2I theo , column in Table 1). This agreement also helps to validate our approach of using geometry scans to locate global minima, since our results closely mirror their lowest energy species.…”
Section: Carbon Dioxide Activationsupporting
confidence: 82%
See 1 more Smart Citation
“…Energies for each minimum and transition state are shown in Table 1. Recently, Illas et al, 21 studied chemically adsorbed CO 2 on the {001} surface of the same series of TMCs and, whilst no other surfaces or states were considered, the available results are in excellent agreement with ours (see 2I theo , column in Table 1). This agreement also helps to validate our approach of using geometry scans to locate global minima, since our results closely mirror their lowest energy species.…”
Section: Carbon Dioxide Activationsupporting
confidence: 82%
“…18 There have been several previous theoretical studies that have confirmed the important role of H 2 O in both reducing the barrier and directing the pathways for CO 2 reduction to methanol on solid state materials. 19,20 Fortunately, carbon dioxide possesses a considerable quadrupole moment, which in the presence of the right catalyst can result in a relatively small barrier for chemical adsorption, 21 due to the strong interaction between the quadrupole moment of carbon dioxide and specific binding sites on the catalyst. Thus, an increased strength of charge-charge, hydrogen-bonding and many other interactions decrease the relative activation barriers by increasing the exothermicity of chemisorbed species, when compared to non-quadrupolar adsorbates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transition metal carbides have attracted attention as promising catalysts for the conversion of CO 2 into CO, methanol, methane, and other hydrocarbons (Nagai et al, 1998b;Solymosi et al, 2002;Porosoff et al, 2014;Posada-Pérez et al, 2014, 2016aXu et al, 2014;Chen et al, 2015Chen et al, , 2016Gao et al, 2016;Liu et al, 2016;Han et al, 2019;Reddy et al, 2019). It has been reported through computational work that transition metal (e.g., Ti, Mo, and V) carbide surfaces are able to uptake and activate CO 2 (Posada-Pérez et al, 2014Kunkel et al, 2016Kunkel et al, , 2018Kunkel et al, , 2019Liu et al, 2017). In liquid phase, metals (Pd, Cu, Co, Fe) supported on Mo 2 C have been tested for the hydrogenation of CO 2 in dioxane under 40 bars, at 135-200 • C (Chen et al, 2015(Chen et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The computational screening of effective solid sorbents by first-principles, combined with a statistical thermodynamics approach, has proven to be a very powerful, predictive tool to accurately estimate the different interaction of a given material with CO 2 and CH 4 , and is used to deliver useful estimates of selectivities and adsorption capacities when posing new materials for biogas upgrading. 8 Presently, density functional theory (DFT) simulations including dispersive forces are the most widely-used approach to compute adsorptive properties of solid materials, being the best balance between accuracy and efficiency for relatively large simulated systems, especially useful to describe CH 4 and CO 2 interactions with a plethora of compounds, including transition metals (TMs), 9,10 transition metal carbides (TMCs), 8,11,12 zeolites, 13 metal-organic frameworks (MOFs), 14 nanoporous carbons, 15 and periodic mesoporous phenylene-silica (MPOs). , are latest additions to the 2D world, 23,24 and have already been tested for a wide variety of applications, including energy storage, 25 water purification, 26 employing the Perdew-Burke-Ernzerhof (PBE) exchangecorrelation functional.…”
mentioning
confidence: 99%